2011
DOI: 10.1007/s00296-011-1969-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine modulators in the treatment of sarcoidosis

Abstract: Sarcoidosis is a granulomatous lung disease in which several cytokines play a pivotal pathogenetic role. Steroid-resistant disease can be treated with immunosuppressive drugs, antimalarial therapies and recently with anti-TNFα agents. The use of biological agents for the treatment of sarcoidosis springs from research into the pathogenesis of the disease and also from the experience of rheumatologists with other chronic inflammatory diseases. Rituximab, golimumab and ustekinumab are cytokine modulators, useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
2
10
0
1
Order By: Relevance
“…Biologic TNF-a antagonists, in particular infliximab, have been effective even in corticosteroid-resistant cases. 143 A therapeutic algorithm for the treatment of cutaneous sarcoidosis based on the limited published literature, reviewed later, and personal experience is included in Fig. 13.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…Biologic TNF-a antagonists, in particular infliximab, have been effective even in corticosteroid-resistant cases. 143 A therapeutic algorithm for the treatment of cutaneous sarcoidosis based on the limited published literature, reviewed later, and personal experience is included in Fig. 13.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…A recent study identified Th17 cells in blood and BAL fluid of patients with active sarcoidosis, suggesting that IL-17-expressing cells may play a role in the alveolitis phase of disease, potentially leading to fibrosis [36,37]. The literature shows that although anticytokine drugs have a rationale based on involvement of various molecules in the pathogenesis of sarcoidosis, there is still no indisputable evidence of their efficacy [39,40].…”
Section: Granuloma Of Sarcoidosis and Cytokines Involved In Pathogenementioning
confidence: 97%
“…However, a placebo-controlled randomized study conducted to evaluate the safety and effectiveness of infliximab in subjects with chronic pulmonary sarcoidosis has not produced the expected results [57,58]. Another randomized placebo-controlled study suggests that infliximab may be beneficial in the treatment of extrapulmonary sarcoidosis in patients already receiving corticosteroids, but authors found no improvement in patients with ocular disease who received infliximab [59].…”
Section: Sarcoidosismentioning
confidence: 99%